Functions modeling change a preparation for calculus - Connally, Eric (Wiley, 2000)
From the Calculus Consortium based at Harvard University, this comprehensible book prepares readers for the study of calculus, presenting families of functions as models for change. These materials stress conceptual understanding and multiple ways of representing mathematical ideas.